A case report of parotid gland epithelioid hemangioendothelioma - Wang, Ke; Hu, Jianhong; Wen, Jiazhu; Zhou, Shuxia; Ye, Linfeng; Fang, Chun; Guan, Jiacheng; Luo, Xiao (Frontiers in Surgery, 2024)
Epithelioid hemangioendothelioma (EHE) is a rare low-grade malignant vascular tumor.It mainly occurs in the liver, lungs, bones, and other parts of the body. Reports of epithelioid hemangioendothelioma in the parotid gland are rare in both domestic and international literature.Here, we present a case report of a parotid gland epithelioid hemangioendothelioma, including its complete clinical course and imaging findings, to improve the diagnosis and treatment of this unusual disease.The patient, a 75-year-old female, presented with a swelling around the right ear for 2 months and pain for 20 days. Enhanced MRI of the parotid gland revealed a well-defined, round mass with homogeneous signal intensity. The mass showed low signal intensity on T1weighted imaging, high signal intensity on T2-weighted imaging, nodular low signal intensity within, significant high signal intensity on DWI sequence, low signal intensity on ADC sequence, and heterogeneous enhancement in the arterial phase after intravenous injection of Gd-DTPA.Nodular non-enhancing low signal intensity was observed internally, and slight clearance was seen in the venous phase. The initial diagnosis before surgery was a benign lesion, but after histopathological and immunohistochemical examination, it was confirmed as epithelioid hemangioendothelioma.Intervention: Complete tumor resection was performed.The patient experienced a favorable recovery, with meticulous follow-up conducted for up to 1 year revealing no signs of recurrence or metastasis. Continued patient surveillance is ongoing to substantiate and validate the long-term efficacy of the treatment.Due to the extreme rarity of parotid gland epithelioid hemangioendothelioma, it often leads to a high misdiagnosis rate. The most common misdiagnosis is salivary gland lymphoma, followed by epithelioid hemangiosarcoma. When the lesion is multifocal, fusiform, with internal necrosis, and shows punctate low signal intensity on T2-weighted imaging, significant enhancement in the arterial phase, particularly with more pronounced peripheral enhancement, and persistent enhancement in the venous and delayed phases, epithelioid hemangioendothelioma should be considered. However, the current clinical diagnosis of epithelioid hemangioendothelioma still primarily relies on immunohistochemical methods.